Faktor–Faktor Yang Mempengaruhi Reputasi Bank Kalbar Di Kota Pontianak - Olimpia Esdi; Muhammad Zalviwan; windi Pratiwi (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2025)
This study aims to determine and analyze the influence of product and service quality, product innovation, integrity and ethics, technological adaptation, service excellence, and user experience on the reputation of Bank Kalbar in Pontianak City. The research applies a quantitative approach using a survey method through questionnaires distributed to Bank Kalbar customers. The data analysis technique used is multiple linear regression. The partial (t-test) results indicate that all independent variables have a positive and significant effect on the bank's reputation (Y), with the following t-values: product and service quality (2.032), product innovation (2.203), integrity and ethics (3.280), technological adaptation (2.551), service excellence (2.111), and user experience (2.727), all of which exceed the t-table value (1.666). Therefore, improvements in these six factors have been proven to strengthen the reputation of Bank Kalbar. The findings of this study are expected to serve as a strategic reference for the bank’s management in enhancing customer trust and loyalty